Public Service Motivation and Service Quality of Local Government Employees: A Moderated Mediation Analysis - Wayu Eko Yudiatmaja (Indonesian Association for Public Administration, 2021)
The study of public service motivation (PSM) is an emerging topic in relation to understanding the impact of perceived service quality within public-sector organizations. Drawing upon the self-determination theory, this paper develops and validates a conceptual model incorporating the relationship between PSM and perceived service quality by the user. Moreover, this study also examines the moderated-mediation models of service factors in the link. This paper further argues user orientation as a mediator in the nexus between PSM and service quality, and service climate as a moderator in the effect of user orientation on service quality. This research was conducted on 250 frontline public servants and their users in Bintan Regency, Kepulauan Riau, Indonesia. The data was performed using structural equation modeling. The proposed model suggests (1) PSM positively related to service quality, (2) user orientation partially mediates the relationship, and (3) the indirect effect of PSM on service quality (via user orientation) is quasi moderated by service climate within the public organization. Accordingly, few theoretical and practical implications for policymakers are formulated.